BRAND NAME AND PAST EXPERIENCE: KEY DRIVERS OF PASSENGER PATRONAGE IN TRANSIT COMPANIES IN SOUTH-SOUTH NIGERIA - Nwankwo, Nwankwo C. O; Fawohunre, Fawohunre F. A; Obasanjo, Obasanjo O. T (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
This study explores the relationship between service experience and passenger patronage of transit companies in the South-South region of Nigeria. The research focuses on commuters’ experiences in transit companies, like commuter and charter services, to understand customers’ perceptions and their impact on customer value and loyalty. Utilizing the Theory of Reasoned Action, the study examines factors such as brand name, pricing, service quality, and past experience as cues for predicting customer experience and how they influence passengers’ patronage decision. The study notes that transportation services are evaluated differently, as they require simultaneous production and consumption, and are intangible and heterogeneous. The study further emphasizes that customer satisfaction is critical to retain and win new customers, and it highlights the importance of valuable research in the service industry in Nigeria. Through a survey research design approach, the study arrived at a sample size of 310 respondents from 47 different public transportation companies operating in the South-South region. The study employed the proportional sampling method to ensure an equal chance of capturing passengers’ experiences across all transporters in the area. The data collected from primary sources through structured questionnaires was analysed using simple regression analysis to test hypotheses at a 0.05 level of significance. The study revealed that the brand name of transporters and past experience are relational dimensions that can predict passenger patronage of transit companies. The empirical results of the study show that the brand name of the transporter and past experiences are significant positive drivers of passenger’s choice of patronising transit companies. The study recommends that transporters should recognise the affiliation between the brand name of their services and passengers’ perceptions of service quality and value. Creating a positive impression during service encounters should be the goal of transporters to maintain a good brand image.